In vitro effects of canine Wharton’s jelly mesenchymal stromal cells and nanoparticles on canine osteosarcoma D17 cell viability. - Reeds, Kimberly (Kansas State University, 2011)
Objectives – To isolate and maintain canine Wharton’s jelly mesenchymal stromal cells (WJMSCs) in culture, to determine the effects of micellar nanoparticles containing doxorubicin (DOX) on WJMSCs and canine osteosarcoma (OSA) D17 cell viability, and to determine the effects of conditioned media from WJMSCs loaded with micellar nanoparticles containing DOX on OSA D17 cell viability. Sample Population – Canine WJMSCs containing various concentrations of DOX micelles and canine OSA D17 cells. Procedures – WJMSCs were isolated from canine umbilical cords. Micellar nanoparticles containing DOX were prepared and added to culture plates containing canine OSA D17 cells to determine micelle effects on cell growth and viability. Conditioned media from culture plates containing canine WJMSCs incubated with various DOX micelle concentrations was added to OSA D17 cells for conditioned media experiments. A 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was performed to assess OSA D17 cell viability. A trypan blue stain was also utilized to perform cell counts to determine the effect of the DOX micelles on stromal cell growth. Results – WJMSCs were successfully isolated and maintained in culture. Micellar nanoparticles containing DOX decreased OSA D17 cell viability. OSA D17 cell viability was also decreased following incubation with conditioned media from canine WJMSCs loaded with micellar nanoparticles containing DOX. Significant decreases with the conditioned media of canine WJMSCs loaded with 10μM micelles occurred at 48 hours (p < 0.005) and at 72 and 96 hours (p < 0.0001). Significant decreases were also observed with the 1 μM DOX micelles at 72 hours (p < 0.005) and 96 hours (p < 0.0001). WJMSC numbers decreased in a dose dependent manner following incubation with DOX micelles. Changes in WJMSC number was not caused by increased cell death as all variables produced similar percentages of dead cells. Conclusions – Canine WJMSCs were successfully isolated and maintained in culture. Stromal cells containing DOX micellar nanoparticles induced OSA D17 cell cytotoxicity while inducing an anti-proliferative, rather than cytotoxic effect, on the WJMSC. These data support future in vivo experiments utilizing canine WJMSCs and micellar nanoparticles.
Keywords: Osteosarcoma; Doxorubicin; Nanoparticles; Wharton's jelly mesenchymal stromal cells; Polymeric micelles; Nanoscience (0565); Oncology (0992); Veterinary Medicine (0778)